2004
DOI: 10.1007/s10040-004-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Radon distribution in groundwater of Taiwan

Abstract: Radon levels were surveyed in 517 monitoring wells constructed in five major groundwater areas of Taiwan. The radon concentration in groundwater samples varied in a wide range from below the detection limit of 18 pCi/L up to 1,100 pCi/L. A worldwide comparison of reported groundwater radon levels was conducted. Overall radon levels in Taiwan groundwater are relatively low compared to other countries because the geology of Taiwan is mainly comprised of sedimentary rocks. Among the 517 wells monitored, only five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Many researchers (e.g. Pane et al, 1995;Han et al, 2006;Surbeck, 2007) discussed the hydrogeological control of radon variations in karstic aquifers and the spatial correlation with changing groundwater levels of the monitoring site due to decreasing or increasing precipitations. In view of their results, it has been found that occasional radon changes in groundwater usually appear in a restricted time of the year announcing the arrival of the new percolating rainwater after the rainfall season.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers (e.g. Pane et al, 1995;Han et al, 2006;Surbeck, 2007) discussed the hydrogeological control of radon variations in karstic aquifers and the spatial correlation with changing groundwater levels of the monitoring site due to decreasing or increasing precipitations. In view of their results, it has been found that occasional radon changes in groundwater usually appear in a restricted time of the year announcing the arrival of the new percolating rainwater after the rainfall season.…”
Section: Resultsmentioning
confidence: 99%
“…Radon isotope ( 222 Rn), for simplicity called "Radon" in the following, is a daughter nuclide of radium ( 226 Ra), which in turn is produced from the decay series of uranium ( 238 U). As a naturally occurring radioactive gas, radon is widely utilized in various fields of earth sciences, such as hydrogeological studies Pane et al, 1995;Han et al, 2006;Surbeck, 2007); detecting buried active faults (Baubron et al, 2002;Al-Hilal and Al-Ali, 2010) and monitoring seismic activities (Teng, 1980;Kuo et al, 2006;Erees et al, 2007). Furthermore, radon method is commonly used in most uranium exploration programmes due to its efficiency, low cost and simplicity (Dyck, 1975;Gingrich, 1984;Jubeli et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, radon levels were high in areas where the fault density varied between 0.58 and 1.2 (FR 2.32). Notably, fault systems located in fracture zones provide a route for radon to migrate upward from deeper sources (Han et al, 2006). Finally, in terms of lithology, the FR analysis yielded higher values, of 200.65, 32.74, and 13.71, for Cretaceous acidic dike (Kad), Cretaceous quartz porphyry (Kqp), and Cambrian quartzite and slate (CEdy) units, respectively.…”
Section: Assessment Of the Contributions Of Each Factor To Model Performancementioning
confidence: 94%
“…Αλ θαη νη πςειέο ζπγθεληξψζεηο ξαδνλίνπ ζην πφζηκν λεξφ κπνξεί λα πξνθαιέζνπλ θίλδπλν γηα ηελ αλζξψπηλε πγεία (Xinwei, 2006) εληνχηνηο ην ζπληζηψκελν φξην πνζηκφηεηαο δελ έρεη αθφκε θαζνξηζηεί, ελψ ζχκθσλα κε νδεγία ηεο USEPA (1999), ε πξνηεηλφκελε ζπγθέληξσζε θζάλεη ηα 150 kBq m -3 . Δικόνα 8.52: α. Ζ αιπζίδα ησλ θπζηθψλ ξαδηελεξγψλ ζηνηρείσλ ηεο ζεηξάο ηνπ 238 U (Surbeck, 2007), β. Ζ ζπγθέληξσζε ηνπ ξαδνλίνπ ζην λεξφ δηάθνξσλ ρσξψλ (ηξνπνπνηεκέλν απφ Han et al, 2006).…”
Section: ζ πηγή ππιάλαunclassified